An innovative seismic-resistant steel frame with reinforced concrete infill walls. (15th June 2017) - Dall'Asta, Andrea; Leoni, Graziano; Morelli, Francesco; Salvatore, Walter; Zona, Alessandro
Highlights: An innovative steel frame with reinforced concrete infill walls is presented. A seismic design procedure for the presented structural system is proposed. Numerical and experimental studies validate its structural behaviour. Abstract: Steel frames with reinforced concrete infill walls (SRCW) are an interesting seismic-resistant structural solution. However, an effective seismic design of SRCWs is not easy due to the current lack of specific capacity design rules that allow controlling the formation of a proper energy dissipating mechanism. In order to overcome such an issue, a ductile design procedure is presented in this paper. The proposed procedure leads to innovative SRCW systems where energy dissipation is expected to take place only in the vertical elements of the steel frame, which are subjected mainly to axial forces. The non-ductile components, i.e. reinforced concrete wall and steel-to-concrete connections, are expected to suffer negligible damage. Accordingly, the system is designed to control the formation of diagonal struts in the infill walls and behaves as a lattice brace instead of a shear wall. Experimental test results and nonlinear finite element analyses are illustrated to support the developed ductile design approach and highlight the advantages of SRCWs.